Patient-reported outcomes : measurement, implementation and interpretation /: measurement, implementation and interpretation. (2014) - Cappelleri, Joseph C; Zou, Kelly H; Bushmakin, Andrew G; Alvir, Jose Ma. J; Alemayehu, Demissie; Symonds, Tara
No abstract available